Biology stage of Moniliophthora roreri in Colombia (2014)
Frosty pod rot disease of cocoa plants is caused by the basiodiomycete Moniliophthora roreri -- Nowadays, this disease is present in almost all Latin American countries producers of cocoa beans, exhibiting high adaptation to diverse environments -- In Colombia, it is the most important disease attacking cocoa crops and the traditional strategies for control have generated side results as strengthening in genetic resistance of strains in some regions -- In this review, we collected the most relevant biological and agricultural aspects of this disease such as origin and distribution of the disease, life cycle, forms of disease control and research projects oriented to understand the genetic and evolution of this pathogen -- Finally, we suggest increasing the number of basic researches, aiming to understand, how this pathogen has evolved its genome in different habitats, favoring its genetic variation -- Thus, with all this knowledge, we could advance in biotechnology programs for control and prevention of the Frosty rod pot